The dynamics of ethical climate: mediating effects of ethical leadership and workplace pressures on organisational citizenship behaviour - O Sookdawoor; A Grobler (Cogent Business & Management, 2022)
The world has been facing unprecedented challenges with various ethical issues within organisations, which is related to ethical leadership and decision making amongst other things. Subsequently, this paper is focused on the interrelationships between organisational culture, ethical organisational climate, ethical leadership, decision making and workplace pressures. The effect of these ethical related constructs on organisational citizenship behaviour, employee ethical behaviour, conduct, and perceived employee performance is further studied, from a macro-meso-micro perspective. This quantitative study used a cross-sectional design and survey strategy. The sample consisted of 526 participants of varying backgrounds working in "large" enterprises across diverse industries in Mauritius. The results of this study show that organisational culture and ethical organisation climate (as macro independent variables) jointly influence the dependent variables (organisational citizenship behaviour, employee ethical behaviour and conduct, and perceived employee performance) both directly and indirectly to varying degrees. It was also found that ethical leadership and decision making, and internal and external workplace pressures (as meso variables) have statistically significant mediating effects on organisational citizenship behaviour and perceived employee performance. The model proved to have a good fit and can be adopted as a guiding model for the business and research communities in fostering organisational citizenship behaviour. Lastly, recommendations were made to enhance the ethical and organisational citizenship behaviour within the corporate environment of Mauritius.
Keywords: 650; ethical leadership; ethical organisational climate; organisational citizenship behaviour; Organisational culture; workplace pressures